1989
DOI: 10.1111/j.1600-0447.1989.tb10301.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric disorders among subjects exposed to a natural disaster

Abstract: A general practice study was carried out in 3 areas of the province of Naples, in southern Italy: Pozzuoli (PZ), a town exposed to significant seismic events in 1983, Monte Ruscello (MR), a village built to accommodate the victims of the earthquake, and Monte di Procida (MP), a town selected as a control since it is situated near PZ and was not significantly affected by the earthquake. The sociodemographic characteristics of the subjects examined were comparable in the 3 areas. The estimate of the real prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 21 publications
6
49
1
2
Order By: Relevance
“…Until now, however, in Japan there has been no analysis relating mental effects to seismic intensity and this valuable data has been used to guide preventive. Elsewhere, researchers have compared the incidence of mental disorder depending on the degree of stress suffered [4][5][6] , but no study has presented quantitative findings on the relationship between the seismic intensity and life events and earthquake stress. To evaluate the usefulness of immediately available seismic intensity information for guiding initial postdisaster mental health activities, we carried out a survey one year after the Great Hanshin-Awaji Earthquake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, however, in Japan there has been no analysis relating mental effects to seismic intensity and this valuable data has been used to guide preventive. Elsewhere, researchers have compared the incidence of mental disorder depending on the degree of stress suffered [4][5][6] , but no study has presented quantitative findings on the relationship between the seismic intensity and life events and earthquake stress. To evaluate the usefulness of immediately available seismic intensity information for guiding initial postdisaster mental health activities, we carried out a survey one year after the Great Hanshin-Awaji Earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…A gradient in the incidence of mental disorders corresponding to quantitative differences in earthquake damage, with the incidence rising towards the epicenter, has been reported [4][5][6] . Previous studies have shown that people who have a higher number of earthquakerelated life events and greater degree of loss experience more frequently develop mental disorders and show severer symptoms [7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Joseph, Andrews, Williams & Yule, 1992;Maj et al, 1989), in 'peripheral victims' of such disasters (Dixon, Rehling & Shiwach, 1993), in helpers in disaster situations (e.g. Duckworth, 1986), in war veterans (e.g.…”
mentioning
confidence: 98%
“…Common survivor problems include sleep disorders, increases in negative health behaviours (e.g. alcohol use and smoking), increased prevalence of subclinical mental health symptoms, and psychiatric disorders, such as posttraumatic stress disorder (PTSD), depression, anxiety and substance abuse [12,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%